Some Implicativities for Groupoids and BCK-Algebras - In Ho Hwang; Hee Sik Kim; Joseph Neggers (Mathematics, 2019)
In this paper, we generalize the notion of an implicativity discussed in <semantics> B C K </semantics> -algebras, and apply it to some groupoids and <semantics> B C K </semantics> -algebras. We obtain some relations among those axioms in the theory of groupoids.